An Analysis of Prejudice in Tayari Jones’s Novel An American Marriage - Ambarwati, Widi; Nasution, Siti Norma (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
In this study, the researchers analyze the forms of prejudice namely stereotype, social distance, and discrimination. This study aims to reveal that literary works reflect social reality. The object of this study is a novel entitled "An American Marriage". In this study the researchers have three problems to discuss: how is the stereotype as a form of prejudice portrayed in Tayari Jones’s novel An American Marriage, how is the social distance as a form of prejudice portrayed in Tayari Jones’s novel An American Marriage, and how is the discrimination as a form of prejudice portrayed in Tayari Jones’s novel An American Marriage. This study used a qualitative descriptive method. Data is obtained from words, phrases, clauses, or sentences that relate to stereotypes, social distance, and discrimination.